STRATEGI PENGEMBANGAN MODEL KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH TSANAWIYAH : Penelitian dan Pengembangan Kepemimpinan Kepala MTS Negeri di Kabupaten Ciamis Propinsi Jawa Barat - M Djaswidi Al Hamdani, - (2003)
The educational service improvement of the State Junior High School (Madrasah Tsanawiyah Negeri - MTs Negeri) is very determined by every person whom involved in the environment of madrasah (Islamic education institution). The improved service will be happened if there were available the attitude of organizational members who commit to the service. Thafs why, Its required the profile of leader who has the ability to motivate through the transformational process of knowledge and providing personality model to make the performance of madrasah as the centre of competitive basic education. The problem of research can be formulated as in ifie Mowing: In what extent (he model development of transformational leadership potential for the principal of MTs Negeri in Ciamis District influence the managerial functions and educational service? The method used in the study is research and development (R & D) with quantitative approach. The analysis of statistical data and testing of hypothesis were done by using the computer assissted program of SPSS version 10.0. The population of research consist of principals, teachers, administrative personnels, and pupils of 17 MTs Negeri in Ciamis District Because the large population, so that rfs done the sampling technique to determine the representative samples. For the internal level of madrasah, the samples consist of 17 principal of madrasah, 17 chairmen of administrative staff, 136 teachers and community members of pupils' parents (Assisstance and Administrating Agent of Education - BP31 Madrasah Committee), or all samples are 170 persons. In accordance with the characteristics of R & D, the findings can be formulated as in the following'. First, the effort and approach estimated have the ability of acceleration to develop the educational service by doing the leadership behavior which is able to motivate the personnel to serve their own tasks, achieving commitment creating the working culture and quality, and developing the *-ansformationafl managerial behavior. The strategies of implementation are training, modular, seminar and workshops, field practice, colleague or partnership clinical ^en jpft Second, to prepare the effective and efficient training require to develop the audience meeting sistematic procedural with the related parlies, deciding the program (structuring the training program, material, approach and meth is, human resources, schedule, and funding). Third, the training implementation and evafluation can be developed by open model system, limited classrooms, and developmental-oriented try out The training implementation and results of their evaluation generally indicate the conclusion based on the quantitative proofs that they provided enough the developmental provisions for MTs by implementing local training for principals of MTs Negeri.In accordance with the results of hypothesis testing, it can be known that there are the significant leadership behavioral changes of MTs Negeri principals in Ciamis District, particularly h their relation to the transformational leadership.The implications of development system for the principals of MTs can be formulated as in the following: The leadership training for MTs Negeri should has been changed by needs assessment for the set of abilities and skins which support the field managerial. One of development models can be implemented in autonomous, local and integrative in the scope of madrasa/i needs.In accordance with the above search findings, so that it can be recommended the implications of research as in the following: (1) the' cal training model is considered effective. Thafs why, the competent officials can do the locals inventarization considered have had the ability to implement the local training by: (a) mapping the needs of MTs principal in short term period, as the applied managerial expertises in madrasah, (b) mapping the needs of MTs principal in long-term period, as the changes anticipation of community demands, creativity and educational innovation, and (c) reinforcing the understanding of educational policies, global trend and morality education; and (2) the transformationai leadership require to be on going developed and integrated into Islamic leadership model because its very significant in managing the potential of madrasah resources. The matter of transformation^ leadership is not in contradiction with the Islamic leadership, in the meaning of one and others are in complementary in educational services. That's why, every leadership development must become the agenda and subject of reviw of educational human resources development for Religious Ministry.